Integrasi Metode Sejarah-Kritis dalam Pendidikan Agama Islam: Penguatan Literasi Keagamaan Kritis di Era Digital - Nimatul Khoeriyah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The development of digital technology and the rapid flow of religious information on social media demand the presence of critical, systematic, and contextual religious literacy in Islamic Religious Education (PAI). This article examines the integration of historical-critical methods including source criticism, isnād-cum-matn methods, and textual archaeology as a methodological framework to improve the quality of PAI learning in the modern era. This research uses a qualitative approach based on literature studies. The results show that the application of historical-critical methods in PAI can strengthen religious moderation, prevent digital radicalism, improve hadith and Qur'an literacy skills, and foster students' critical thinking skills. This article recommends the gradual and proportional pedagogical implementation of historical-critical methods in the PAI curriculum.